Combined Curcumin and Lansoprazole-Loaded Bioactive Solid Self-Nanoemulsifying Drug Delivery Systems (Bio-SSNEDDS) - Abdulrahman Alshadidi; Ahmad Abdul-Wahhab Shahba; Ibrahim Sales; Md Abdur Rashid; Mohsin Kazi (Pharmaceutics, 2021)
Background: The current study aimed to design a novel combination of lansoprazole (LNS) and curcumin (CUR) solid oral dosage form using bioactive self-nanoemulsifying drug delivery systems (Bio-SSNEDDS). Methods: Liquid SNEDDS were prepared using the lipid-excipients: Imwitor988 (cosurfactant), Kolliphor El (surfactant), the bioactive black seed (BSO) and/or zanthoxylum rhetsa seed oils (ZRO). Liquid SNEDDS were loaded with CUR and LNS, then solidified using commercially available (uncured) and processed (cured) Neusilin® US2 (NUS2) adsorbent. A novel UHPLC method was validated to simultaneously quantify CUR and LNS in lipid-based formulations. The liquid SNEDDS were characterized in terms of self-emulsification, droplet size and zeta-potential measurements. The solidified SNEDDS were characterized by differential scanning calorimetry (DSC), X-ray powder diffraction (XRD), scanning electron microscopy (SEM), in vitro dissolution and stability in accelerated storage conditions. Results: Liquid SNEDDS containing BSO produced a transparent appearance and ultra-fine droplet size (14 nm) upon aqueous dilution. The solidified SNEDDS using cured and uncured NUS2 showed complete solidification with no particle agglomeration. DSC and XRD confirmed the conversion of crystalline CUR and LNS to the amorphous form in all solid SNEDDS samples. SEM images showed that CUR/LNS-SNEDDS were relatively spherical and regular in shape. The optimized solid SNEDDS showed higher percent of cumulative release as compared to the pure drugs. Curing NUS2 with 10% PVP led to significant enhancement of CUR and LNS dissolution efficiencies (up to 1.82- and 2.75-fold, respectively) compared to uncured NUS2-based solid SNEDDS. These findings could be attributed to the significant (50%) reduction in the micropore area% in cured NUS2 which reflects blocking very small pores allowing more space for the self-emulsification process to take place in the larger-size pores. Solid SNEDDS showed significant enhancement of liquid SNEDDS stability after 6 months storage in accelerated conditions. Conclusions: The developed Bio-SSNEDDS of CUR and LNS using processed NUS2 could be used as a potential combination therapy to improve the treatment of peptic ulcers.